2020
DOI: 10.3390/ma13102302
|View full text |Cite
|
Sign up to set email alerts
|

AFM-Based Method for Measurement of Normal and Osteoarthritic Human Articular Cartilage Surface Roughness

Abstract: In osteoarthrosis, pathological features of articular cartilage are associated with degeneration and nanomechanical changes. The aim of this paper is to show that indentation-atomic force microscopy can monitor wear-related biomechanical changes in the hip joint of patients with osteoarthritis. Fifty patients (N = 50), aged 40 to 65, were included in the study. The mechanical properties and the submicron surface morphology of hyaline cartilage were investigated using atomic force microscopy. Measurements of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…It was observed that each 60 μm change in indenter location could result in a twentyfold variation of the measurement [ 66 ]. Our previous research carried out to 450 nm in depth [ 67 ] shows that the surface is more suitable to diagnose, so in this study, we measured the mechanical properties of cartilage surface to 150 nm in depth. However, the statistical significance of the results was observed below 100 nm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that each 60 μm change in indenter location could result in a twentyfold variation of the measurement [ 66 ]. Our previous research carried out to 450 nm in depth [ 67 ] shows that the surface is more suitable to diagnose, so in this study, we measured the mechanical properties of cartilage surface to 150 nm in depth. However, the statistical significance of the results was observed below 100 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies of articular cartilage have assumed a wide range of Poisson’s ratios [ 63 , 64 ]. In this study [ 67 ], the local Poisson’s ratio was assumed to be 0.5 for articular cartilage based on previous experimental reports. The changes in articular cartilage structure result in deterioration of the mechanical strength [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study we have demonstrated that by scanning the FBG sensor across a sample surface, it is indeed capable of detecting and quantifying elasticity gradients of the sample [ 22 ]. In addition, our results emphasize that the FBG sensor is potentially able to detect early OA even before the surface roughness of the cartilage is increased due to wear-related changes, which is crucial for other AFM-based approaches to detect the onset of OA [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bioprinting seeks to replicate the broad range of stiffnesses exhibited in native tissues, as for example the lung (0.2-2 kPa) and cartilage (500-1700 kPa). [41,42] Various biofabrication techniques have achieved these mechanical properties using gelatin and its derivatives. [35,43] To realize an equally broad spectrum of mechanical properties in TPS printed ECM derived scaffolds would hence be highly desirable.…”
Section: Introductionmentioning
confidence: 99%